Organoboron compounds. XVII. Preparation and hydrolytic properties of some substituted borazines containing fluoreseent groups - Molinari, Marcelo Antonio; McCusker, Patrick A. (American Chemical Society, 1964)
Fil: Molinari, Marcelo Antonio Comisión Nacional de Energía Atómica; Argentina